Analysis of Understanding Tax Regulations, Modern Tax Administration, and Accountability to Community Taxpayer Compliance - Tri Raharjanto (Enrichment : Journal of Management, 2021)
This study aimed to analyze tax regulations, modern tax administration, and accountability for public taxpayer compliance. This research uses quantitative research with a descriptive analysis approach. The types of data used in this research are primary and secondary data. The population in this study are individual taxpayers who are registered at the Sumedang district tax office who do business and work independently. The sampling technique in this study used the convenience sampling method. Data collection techniques using the questionnaire method and testing the research data using validity test, reliability test, descriptive statistical test, and statistical t-test. Based on the analysis of the research data, the following points can be concluded: a) The relationship between understanding of tax regulations and taxpayer compliance is positive and significant with a T-count of 3.102 and the original sample value of 0.388; b) The relationship between Modern Tax Administration and Taxpayer Compliance is positive and significant with a T-count of 3.504 and the value of the original sample is 0.385, and c) The relationship between Accountability and Taxpayer Compliance is positive and significant with a T-count of 3.095 and the original sample value of 0.281.